Stream ecosystem health in rural mixed land-use watersheds. Issue 5 (1st September 2008) - Gordon, Robert; Jamieson, Rob; Stratton, Glen; Madani, Ali; Brisbois, Marie Claire
Abstract : A paired stream approach was used to assess ecosystem health in two rural Nova Scotia streams (Thomas Brook and Sharpe Brook) with varying land-use practices. The objectives of the study were to assess stream health within an agricultural catchment, the Thomas Brook Watershed, and to identify parameters that could be used to characterize the impacts of agricultural land use on stream ecosystem health within intensively farmed watersheds in Nova Scotia. General water quality (nutrient concentrations, turbidity, pH, temperature) and the hydrology of both watersheds were monitored from May to October 2006. In addition, continuous dissolved oxygen (DO) and chlorophyll a data were collected in both streams, and benthic invertebrate populations were characterized during the study period. Diurnal DO data were analyzed to determine photosynthesis and respiration ratios. Macroinvertebrate data provided information on productivity, and on a number of other relevant metrics. Findings determined that agricultural land-use generally led to high nutrient concentrations, large dissolved oxygen variability, turbid waters, high chlorophyll a content, and impacted macroinvertebrate populations in streams. Forested land-use demonstrated typically unimpacted conditions. It was concluded that DO dynamics and macroinvertebrate metrics would be very useful for providing a generalized assessment of stream health in agricultural watersheds.